Cool Tools in the Kitchen. - Kelly, Kevin, 1952- (O'Reilly Media, Inc., 2011)
Cool tools really work. A cool tool can be any tried-and-true book, gadget, software, video, map, hardware, material, or website. The reviews in this book were written by those of us who have actually used the tool and others like it. We only review things--old or new--that we like and ignore the rest. This is a curated collection of the best cool tools for the Kitchen. It is not intended as a shopping list or checklist. Consider this a jumping-off point for thinking and re-thinking about what's possible in your kitchen. Some kitchens can certainly operate with fewer and/or different tools; som.